2013
DOI: 10.1186/2046-4053-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement in prevention programs of mother to child transmission of HIV: a systematic review to identify barriers and facilitators

Abstract: BackgroundMany reports point to the beneficial effect of male partner involvement in programs for the prevention of mother-to-child-transmission (PMTCT) of HIV in curbing pediatric HIV infections. This paper summarizes the barriers and facilitators of male involvement in prevention programs of mother-to-child-transmission of HIV.MethodsWe searched PubMed, EMBASE, CINAHL and the Cochrane Central Register of Controlled Trials (CENTRAL) for studies published in English from 1998 to March 2012. We included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
225
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(252 citation statements)
references
References 42 publications
(227 reference statements)
24
225
2
1
Order By: Relevance
“…Inviting men to the hospital for voluntary counselling and HIV testing and offering of PMTCT services to men at service sites other than antenatal care were key health system actions. Prior HIV testing and knowledge on HIV can also facilitate their involvement [12,14,15]. Social desirability and recall biases were possibly limitations of this study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Inviting men to the hospital for voluntary counselling and HIV testing and offering of PMTCT services to men at service sites other than antenatal care were key health system actions. Prior HIV testing and knowledge on HIV can also facilitate their involvement [12,14,15]. Social desirability and recall biases were possibly limitations of this study.…”
Section: Discussionmentioning
confidence: 93%
“…According to different studies [11,12], other reasons for low male partner involvement were long waiting times at the antenatal care clinic, the male unfriendliness of PMTCT services, lack of communication among couples, reluctance of men to know their HIV status, misconception by men that their spouse's HIV status was a proxy of theirs, and lack of willingness among women to get their partners involved due to fear of domestic violence, stigmatization or divorce. According to qualitative study done in Blantyre, Malawi [13] to explore the relevance of male involvement in the prevention of mother to child transmission of HIV, male partners involvement in PMTCT were associated with the uptake of interventions along the PMTCT cascade and education strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in Malawi, Tanzania and Kenya also report low male participation rates ranging from 3.5% to 16% [17][18][19].While male involvement in ANC and PMTCT of services resulted in increased uptake of antenatal care services in Nepal and United States of America [20][21][22], increase uptake and adherence to PMTCT interventions in Tanzania and Kenya [18,23] uptake of HIV testing by women in Tanzania and Uganda [24,25] an opportunity of male testing in Burkina Faso [26]. Recent systematic review has identified barriers to male involvement in PMTCT programs in sub-Saharan Africa [27,28]. In East, Central and West Africa common barriers cited were sociocultural in nature (including gender inequality and normative social roles that limited male participation), deficits in HIV or ANC knowledge, a health system infrastructure or culture that discouraged male engagement, or personal characteristics, including age or occupation associated with willingness to engage in PMTCT [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic review has identified barriers to male involvement in PMTCT programs in sub-Saharan Africa [27,28]. In East, Central and West Africa common barriers cited were sociocultural in nature (including gender inequality and normative social roles that limited male participation), deficits in HIV or ANC knowledge, a health system infrastructure or culture that discouraged male engagement, or personal characteristics, including age or occupation associated with willingness to engage in PMTCT [28][29][30][31]. Several studies highlight cultural barriers related to gender power dynamics wherein men perceive ANC to be the sole responsibility of women and gender norms that disapprove of males engaging in antenatal care activities [18,25,28,32,33].…”
Section: Discussionmentioning
confidence: 99%